PENERAPAN PEMBELAJARAN COOPERATIVE LEARNING TIPE TAI BERMEDIAKAN PERMIANAN AKTIF UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA - Hidayatulloh, Maulana Rohmat; Herimanto, Herimanto; Isawati, Isawati (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2017)
The purpose of this study is to improve the activity and learning outcome of class X IIS 3 SMAN 1 Banyudono through the implementation of Team Assisted Individualization (TAI) with Active Gaming Media.Data and data sources come from students, teachers, and the learning process. The data collection technique is by interviews, observations, questionnaires and tests. Test method validation using triangulation techniques, data analysis using comparative descriptive technique.The results of this study indicate that: (1) the application of learning models TAI with Active Gaming Media can improve the activity of the students. This can be seen in the percentage of achievement indicators of students learning activeness in the questionnaire, on the pracycle percentage of activity just touch 54,28% and then at the first cycle the average achievement of students' learning activeness amounted to 74.98% and the second cycle increased to 81.20%, this acquisition meets the achievement indicators for 75%; (2) application of learning models TAI with Active Gaming Media can improve student learning outcomes. It daat seen in the percentage of the value of cognitive test results on the first cycle that show 47.82% increased in the second cycle to 100%, these results have exceeded the target of achieving set at about 90%.Conclusions from this research is the application of learning models TAI with Active Gaming Media can improve the studentactivity and learning outcome.